An assessment of the contributions of Afrikaner, Hereford and Simmentaler in composite breed development in beef cattle - Skrypzeck, Heidi (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2000.